2014
DOI: 10.3171/2014.7.focus14317
|View full text |Cite
|
Sign up to set email alerts
|

Expanding indications for the extended endoscopic endonasal approach to hypothalamic gliomas: preliminary report

Abstract: Object In the last decade the indications for the endoscopic endonasal approach have been progressively expanded to include lesions that have not been traditionally considered amenable to resection through the transsphenoidal route. In this study, the authors analyze their experience with hypothalamic gliomas treated via the endoscopic endonasal approach. Methods Consecutive cases of hypothalamic gliomas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 32 publications
0
13
0
1
Order By: Relevance
“…The recommended practice is to open the arachnoid over the part of the tumour that is visible. If the surgery is performed in order to obtain a biopsy sample, a Weil forceps is used to remove small fragments, while haemostasis is achieved with bipolar coagulation [4]. For tumour removal, hydro-dissection seemed particularly useful for exploring and removing residues in our case.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The recommended practice is to open the arachnoid over the part of the tumour that is visible. If the surgery is performed in order to obtain a biopsy sample, a Weil forceps is used to remove small fragments, while haemostasis is achieved with bipolar coagulation [4]. For tumour removal, hydro-dissection seemed particularly useful for exploring and removing residues in our case.…”
Section: Discussionmentioning
confidence: 99%
“…For a complete tumour resection combined with minimal post-surgical morbidity, ExTSS allows us to have maximum exposure of the operating field and to identify the anatomical relationships between the tumour and surrounding structures. We followed a similar technique to that described by Zoli et al [4]. Zoli et al [4] highlighted that when considering an endoscopic endonasal approach to the third ventricle, it is crucial to ascertain the position of the chiasm relative to the tumour and the tuberculum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zoli et al reported that this approach is useful in hypothalamic gliomas for central debulking and even gross-total removal of the tumor. 38) Their initial experience may suggest that the endoscopic endonasal approach may allow the surgeon to remove the tumor with a microsurgical technique as well. However, their study includes only a small number of patients and the method remains only a possibility at this time.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to typical skull base tumors, such as pituitary adenomas, chordomas, craniopharyngiomas, or meningiomas, resection of hypothalamic gliomas was described. 8 In all these procedures surgical hemostasis is achieved by bipolar coagulation. There are many prerequisites for bipolar coagulations forceps in general, but a few more are added during EETS.…”
Section: Discussionmentioning
confidence: 99%